Desain Industri Refleksi Spirit Dinamika Jaman - Baskoro Suryo Banindro (Institut Seni Indonesia Yogyakarta, 2015)
Industrial design has become a part of visual culture and penetrates all sides of human life. As a scientific, profession, and maa production. its exixtence has caused the emergence of great industrial designers, monumental industrial products, renewable techniques, and materials, fashionable models that can be considered as reality and reflection of an era dynamics. Industrial design has resulted not only mas products but also aesthetic styles, streams, and idioms that transformed them into universal trends of design.Keywords: industrial design, representation, spirit of age